Volatile free liquid membranes for electromembrane extraction - Šlampová, Andrea; Kubáň, Pavel (Analytica chimica acta, 2021)
Volatile solvents are excellent extraction media for liquid-liquid extractions. However, their use in supported liquid membranes (SLMs) is limited by their evaporation from SLM and thus poor SLM stability and they have never been considered truly useful for electromembrane extraction (EME). In this contribution, volatile solvents were systematically investigated as liquid membranes for EME and their extraction characteristics were comprehensively examined for the first time. A short plug of a water immiscible volatile solvent (a free liquid membrane (FLM)) was sandwiched between two aqueous plugs (donor and acceptor solutions) in a narrow-bore polymeric tubing. Evaporation of the volatile FLM was thus completely avoided and excellent stability of the phase interface was ensured. Suitability of volatile FLMs for EMEs was justified by μ-EMEs of nortriptyline, haloperidol, loperamide and papaverine as model non-polar basic drugs. Extraction performance of μ-EME through ethyl acetate was comparable or better to that through standard non-volatile EME solvents and a high extraction selectivity was achieved for nortriptyline and haloperidol extracted through chloroform. μ-EMEs through the volatile FLMs were characterized by high extraction recoveries (62%-99% for standards and 40-89% for body fluids), low electric currents (10-1380 nA), no susceptibility to matrix ions and suitability for pretreatment of raw body fluids (human urine and serum). Resulting extracts were analysed by capillary electrophoresis with ultraviolet detection (CE/UV). Repeatability of the μ-EME-CE/UV method was excellent with intra-day and inter-day RSD values 0.8-3.2% and 1.8-4.6%, respectively. Further experiments demonstrated additional advantages of volatile FLMs by nearly exhaustive μ-EMEs of atenolol as the polar basic drug with no need for FLM modification by ionic carriers. The presented comprehensive examination of volatile solvents has broadened the range of liquid membranes suitable for EME and it is believed that this proof-of-concept study will stimulate further interest in a deeper investigation of volatile phase interfaces in EME.
Keywords: léčivé přípravky; Membranes, Artificial; elektřina; rozpouštědla; Humans; lidé; membrány umělé; Electrophoresis, Capillary; Pharmaceutical Preparations; elektroforéza kapilární; Solvents; Electricity